Alisher Navai about Khoja Ahmad Yassawi and his followers (Journal of Oriental Studies, 2020)
In written and oral Turkic literature, it was a tradition to write about the virtues of moral figures, which are considered the spiritual pillars of the people, to express in their works their merits to society. As is known from history, one of the prominent figures of Turkic literature, Alisher Navai, in some of his works attached particular importance to the life stories, works and actions of mystics and sheikhs of the Tariqat (Sufi order), issues of Sufism and Tariqat as a whole. In particular, in his work, known in Eastern literature under the name “Nasaim ul-Muhabbat”, he gave information about the famous seven hundred Sufist of the Turkic-Islamic world and about poets, writers and Sufis. In this book we can see a respectful attitude towards Ahmad Yassawi, to a number of his successors and followers who continued the teaching of order Yassawism. It focuses on their life stories, the wonders of discovery, public and public services, their virtues and spiritual characteristics, as well as quotes from their meaningful wise words. As is known from history, Ahmad Yassawi has been one of the most important names in the history of Turkic Sufism and literature for centuries. The school of Yassawism and Hikmat, which he founded, has been important in Sufism and literature for hundreds of years. The article will explain modest ideas and thoughts on this issue. Key words: Khoja Ahmеd Yassawi, Yassawism, Literature, Hikmat, Alisher Navai, Turkestan, Work.